Resource saving wool washing technology - Oseiko, Мykola; Romanovska, Tetiana (My University, 2017)
Introduction. Washing of wool is carried out in an aqueous environment in order to remove contaminants and wool fat (zhyropit). Remove sewage from sewage. The purified fat of wool (food additive E913, lanolin) is widely used in the production of food, perfumery, cosmetics and specialty products and preparations. Materials and methods. Sles 70 was washed with wipes. To find rational wool washing parameters, the mathematical planning of the experiment was performed using Latin squares. Experimental data was processed using mathematical statistics in the Matcad package. Results and discussion. The influence of Sles 70 concentration in the washing solution in the range of 0.53.5 g/dm3, the hydromodule 1050, the temperature 2050 °С and the duration of washing 2 to 32 minutes were determined for extraction of extractives from sheep wool into a washing solution. The rational parameters of washing of fine-wool hair are revealed, influential factors are determined. The possibility of reducing the amount of water used during washing is studied. A regression equation is obtained that approximates the effect of normalized factors on the refractive index n (nD 20) of waste water. Three essential and significant factors on the amount of extracted substances extracted in the washed solution are selected. The most influential factor on the refractive index of the spent washing solution is the temperature. Further on the significance of the effect is the hydromodule, with the temperature and the hydraulic module exhibit a measurable effect on the refractive index. The less important factor is the duration of the washing process. The concentration of detergent Sles 70 was an ineffective factor in the process of washing the wool, since the detergent was sufficient to form a micelle in a clean solution. Conclusions. It is determined that within the limits of the investigated range, the rational mode is as follows: washing at a temperature of 40 °С and a hydromodule of process 10 (the ratio of aqueous solution: wool 10:1) for a duration of 10 minutes washing solution Sles 70 at a concentration of 1 g/dm3. Вступ. Миття вовни здійснюють у водному середовищі з метою видалення забруднень та вовняного жиру (жиропоту). З відпрацьованої мийної води вилучають жир. Очищений вовняний жир (E913, ланолін) широко використовують під час виготовлення харчових, парфумерно-косметичних і спеціальних продуктів і препаратів. Матеріали та методи. Досліджували миття овечої вовни мийним засобом Sles 70. Для пошуку раціональних параметрів миття вовни застосували математичне планування експерименту за латинськими квадратами. Експериментальні дані обробляли методами математичної статистики у пакеті Matcad. Результати та обговорення. Визначали вплив концентрації Sles 70 у мийному розчині у діапазоні 0,53,5 г/дм3, гідромодуля 1050, температури 2050 С і тривалості миття 232 хв. на вилучення з овечої вовни екстрактивних речовин у мийний розчин. Виявлено раціональні параметри миття тонкорунної вовни, Визначено впливові фактори. Вивчено можливість зменшення кількості води, яку використовують під час миття. Отримано рівняння регресії, що апроксимує вплив нормалізованих факторів на показник заломлення nD 20 відпрацьованої мийної води. Відібрано три суттєво впливові та значущі фактори на кількість вилучених екстрактивних речовин у мийному відпрацьованому розчині. Найвпливовішим фактором на показник заломлення відпрацьованого мийного розчину є температура. Далі за значущістю впливу є гідромодуль, причому температура і гідромодуль виявляють сумірний вплив на показник заломлення. Менш впливовим фактором є тривалість процесу миття. Невпливовим фактором на процес миття вовни виявилася концентрація мийного засобу Sles 70, оскільки мийного засобу було достатньо для утворення міцел у мийному розчині. Висновки. У межах дослідженого діапазону раціональним режимом є такий: миття за температури 40 С і гідромодуля процесу 10 (співвідношення водний розчин : вовна 10:1) тривалістю 10 хв. мийним розчином Sles 70 концентрацією 1 г/дм3.
Keywords: wool; вовна; grease; жир; washing; миття; resourcesaving; ресурсозбереження; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів